2018
DOI: 10.1177/0333102418776017
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1, randomized, parallel-group, double-blind, placebo-controlled trial to evaluate the effects of erenumab (AMG 334) and concomitant sumatriptan on blood pressure in healthy volunteers

Abstract: Co-administration of erenumab and sumatriptan had no additional effect on resting blood pressure or on pharmacokinetics of sumatriptan. Trial registration: ClinicalTrials.gov, NCT02741310.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…A lack of BP‐increasing effects after CGRP‐inhibition is supported by studies with small‐molecule CGRP receptor antagonists, where there is no evidence of vasoconstriction after CGRP receptor blockade . Further, there was no additional increase in BP observed with erenumab in a recent study with the primary objective to evaluate the safety of concomitant use of sumatriptan and erenumab …”
Section: Discussionmentioning
confidence: 96%
“…A lack of BP‐increasing effects after CGRP‐inhibition is supported by studies with small‐molecule CGRP receptor antagonists, where there is no evidence of vasoconstriction after CGRP receptor blockade . Further, there was no additional increase in BP observed with erenumab in a recent study with the primary objective to evaluate the safety of concomitant use of sumatriptan and erenumab …”
Section: Discussionmentioning
confidence: 96%
“…36 Furthermore, there was no effect of combination erenumab and sumatriptan on blood pressure compared to sumatriptan alone in a phase 1 study. 37 These studies, in combination with the decrease in triptan use, indicate a lack of effect of erenumab on the effectiveness of triptans as acute migraine treatment, which one would expect triptan use to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 1 trials showed that erenumab was well tolerated, including when combined with triptans; also, cardiovascular safety was demonstrated in patients with stable angina 8‐10 . In other studies, erenumab was well tolerated; injection‐site reactions and constipation were the main adverse effects, affecting approximately 3% of patients 8,9,11‐15 . Phase 2 and phase 3 trials of erenumab as a preventive treatment for episodic migraine with open‐label extension and a phase 2 trial of erenumab for chronic migraine demonstrated a significant reduction in MMD, a 50% responder rate of 30‐65%, and reduced abortive use 12,13,15‐17 …”
Section: Introductionmentioning
confidence: 99%